Ultrasound-guided combined femoral-sciatic-obturator nerve block versus sub-arachnoid block in anterior cruciate ligament (ACL) reconstruction: A randomized single-blind study - Mohan Bhattrai, Kushal; Pahari, Thaneswar; Hirachan, Rozeeta; Neupane, Sandeep; KC, Unika (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Ultrasound-guided combined femoral-sciatic-obturator nerve block (peripheral nerve block) is the preferred technique in anterior cruciate ligament reconstruction because it avoids subarachnoid block (SAB) related complications and ensure prolonged postoperative analgesia. The aim of the study was to compare ultrasound-guided peripheral nerve block and SAB for anterior cruciate ligament (ACL) reconstruction. Methods: A randomized, single-blind study was conducted among patients undergoing ACL reconstruction at our center from February through November 2024. Fifty patients undergoing the procedure were randomly assigned to either receive SAB- 2 ml of 0.5% hyperbaric bupivacaine (group A) or ultrasound-guided combined femoral-sciatic-obturator nerve block- 30 ml mixture of 5 ml 2.0% lidocaine, 15 ml 0.5% bupivacaine plus 10 ml distilled water (group B). Hemodynamic changes, visual analogue score (VAS), time-to-spontaneous micturition following surgery, time to return motor power and time to rescue analgesia were compared between the groups. Results: In Group A, the mean VAS was 2.32±0.69 and 5.48±0.82 after 2 and 3 hours respectively, whereas the VAS was zero in group B throughout. The time to first rescue analgesia was significantly longer in Group B (630.4±36.11 min) when compared to Group A (248.4±26.09 min). Conclusions: Ultrasound-guided combined femoral-sciatic-obturator nerve block provided better hemodynamic stability, prolonged postoperative analgesia and allowed early ambulation due to early return of motor power.